Left ventricular deformation at rest predicts exercise‐induced elevation in pulmonary artery wedge pressure in patients with unexplained dyspnoea. (22nd November 2016) - Biering‐Sørensen, Tor; Santos, Mário; Rivero, Jose; McCullough, Shane D.; West, Erin; Opotowsky, Alexander R.; Waxman, Aaron B.; Systrom, David M.; Shah, Amil M.
Abstract: Aims: Impaired left ventricular (LV) deformation despite preserved LV ejection fraction (LVEF) is common and predicts outcomes in heart failure with preserved LVEF. We hypothesized that impaired LV deformation at rest is a marker of impaired cardiac systolic and diastolic reserve, and aimed to determine whether resting longitudinal (LS) and circumferential strain (CS) are associated with invasively measured haemodynamic response to exercise in patients with dyspnoea and a normal LVEF. Methods and results: We studied 85 patients with LVEF ≥50% and free of significant valvular disease who were referred for evaluation of dyspnoea. All patients underwent rest echocardiography followed by right heart catheterization and cardiopulmonary exercise testing with concomitant invasive haemodynamic monitoring. The LS, CS and CS/LS ratio were measured by two‐dimensional speckle‐tracking echocardiography at rest. Lower absolute LS at rest was associated with greater increase in pulmonary arterial wedge pressure (PAWP) from rest to peak exercise ( r  = 0.23, P  = 0.034). In contrast, higher absolute CS at rest predicted a greater increase in PAWP ( r  = − 0.27, P  = 0.032) and greater stroke volume augmentation with exercise ( r  = − 0.26, P  = 0.021). Higher CS/LS ratio was most predictive of elevation in PAWP with exercise ( r  = 0.30, P  = 0.015). Of the measures of LV systolic and diastolic function assessed, the CS/LS ratio resulted in the highest area under the curve and specificity for the presence of rest‐ or exercise‐induced pulmonary venous hypertension. Conclusion: Left ventricular deformation at rest predicts exercise‐induced rise in PAWP among patients with dyspnoea and a preserved LVEF. A pattern of rest deformation characterized by worse LS and exaggerated CS is most strongly associated with exercise‐induced rise in PAWP.